2009
DOI: 10.1186/cc8172
|View full text |Cite
|
Sign up to set email alerts
|

Complications of continuous renal replacement therapy in critically ill children: a prospective observational evaluation study

Abstract: IntroductionContinuous renal replacement therapy (CRRT) frequently gives rise to complications in critically ill children. However, no studies have analyzed these complications prospectively. The purpose of this study was to analyze the complications of CRRT in children and to study the associated risk factors.MethodsA prospective, single-centre, observational study was performed in all critically ill children treated using CRRT in order to determine the incidence of complications related to the technique (pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
68
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(73 citation statements)
references
References 28 publications
4
68
1
Order By: Relevance
“…Santiago et al reported that 30% of patients on CRRT developed hypotension in the hour following initiation of treatment, similar to the 43% observed in our study [17] . Electrolyte abnormalities have also been previously described.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Santiago et al reported that 30% of patients on CRRT developed hypotension in the hour following initiation of treatment, similar to the 43% observed in our study [17] . Electrolyte abnormalities have also been previously described.…”
Section: Discussionsupporting
confidence: 81%
“…Hypotension and electrolyte disturbances following initiation of CRRT have been reported as the most common AEs [5,12,17] . Various studies have described the individual AEs, safety and usefulness of CRRT in critically ill patients over the last decade [15,17,18] , especially in children [17,[19][20][21] .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In a case series of 174 children requiring CRRT, hypotension on connection was detected in 53 patients (30.4%) [16]. Extracorporeal circuit priming volume ideally should not exceed 10% of a patient's circulating blood volume in order to avoid acute blood depletion from the circulation at the start of the extracorporeal treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In adults and children, some of the complications that can sometimes arise with eRRT include intradialytic hypotension (IDH), hemorrhage, electrolyte disturbances, hypothermia, and thrombocytopenia [7][8][9]. Although these complications have been clinically observed in CRRT in critically ill neonates, few reports have focused on complications during CRRT [10,11].…”
Section: Introductionmentioning
confidence: 99%